The Innovation Potential of Living-Labs to Strengthen Small and Medium Enterprises In Regional Australia - Dhakal, S.; Mahmood, M.; Wiewora, A.; Brown, Kerry; Keast, R. (Australia and New Zealand Regional Science Association International Inc., 2013)
The small and medium enterprise (SME) sector has been the major source of well-being and employment opportunities in regional Australia. Consequently, fostering the innovative capacity of SMEs in regions that are struggling to grow their economies and distribute the growth fairly while not degrading the environment has never been more important. While SMEs generally face more uncertainties in relation to resources (e.g. financial, human and social capital) when compared to larger businesses, collaborative, cutting-edge mechanisms to enhance innovation capabilities of regional SMEs are lacking. This paper responds to this gap and proposes a Living Laboratory – an open, multi-disciplinary and multi-stakeholder action research platform where innovations can be co-created, tested and evaluated in the every-day environment of SMEs – as a way to strengthen the SME sector in regional Australia.